Interaction between Meropenem and Valproate: Not to overlook - Hafeez , Qurat-ul-Ain (International Journal of Endorsing Health Science Research, 2016)
Background Valproic acid is commonly used to treat various types of seizures and follows non-linear pharmacokinetics with a therapeutic range of 50 – 150 ug/ml. Several retrospective studies have reported that concomitant administration of VPA and carbapenem lead to decrease in VPA levels significantly and results in failure of seizure control. Different studies suggest the mechanism of interaction as (i) carbapenem may inhibit the gastrointestinal absorption of VPA (ii) meropenem accelerated the glucuronidation of VPA to VPA glucuronide (VPA-G) and inhibited the hydrolysis of VPA-G back to the VPA thus increasing the clearance of VPA and VPA-G and (iii) due to fast erythrocyte distribution of VPA by carbapenem, VPA levels has been reduced. Purpose To report four cases who were maintained on therapeutic levels of VPA and had sub-therapeutic levels afterward due to the administration of meropenem. Method through CPOE system of AKUH the cases in 2014 were identified who were on valproate-meropenem combination with the available pre and post meropenem valproate levels. Result Patients of different age group showed significant reduction in VPA levels within 48 hour of administration of meropenem. Conclusion This case series describing the clinical importance of this probable drug interaction and promote its awareness among physicians in Pakistan. If a patient was therapeutic on the same dose of valproate and need broad spectrum coverage, a dose adjustment of valproate should not be done and physicians should consider either alternative broad spectrum antibiotic or renaly cleared antiepileptic to avoid this frequently used dangerous drug combination.